The army and the microworld: Computers and the politics of gender identity. - Edwards, P.N. (Signs: Journal of Women in Culture & Society)
Examines the increase of American women in the computer programming and systems analysts field since the 1970s. Modes of thinking with machines; Computers and strategic thinking; Gender, computers, and the military; Computers and war futures.